Optimalisasi Platform Pembelajaran Fisika Online melalui Pelatihan Guru untuk Meningkatkan Motivasi Belajar Siswa SMP - Maria Yuliana Kua; Afrianus Gelu; Sentot Kusairi; Frederikus Ngongo (I-Com: Indonesian Community Journal, 2025)
The digital transformation in education necessitates that physics teachers possess the ability to integrate technology into the teaching and learning process to enhance students’ motivation and active engagement. Nevertheless, in Ngada Regency, junior high school physics teachers continue to encounter challenges in effectively utilizing online learning platforms. This community engagement program aimed to enhance the digital competence of physics teachers through structured training and mentoring on the use of digital learning platforms, including Google Classroom, Canvas, Padlet, Kahoot!, Nearpod, and Genially. The program was implemented in collaboration with six partner schools using a combination of workshops and mentoring approaches. The findings indicate a substantial improvement in teachers’ digital literacy and self-efficacy in designing technology-enhanced physics instruction. On average, post-test scores increased by 37%, all participants acknowledged the program’s benefits, and the majority expressed readiness to regularly adopt digital platforms in their teaching practices. This program offers a strategic model for capacity building among teachers in regions confronting challenges in the digital transformation of education.